Parameterization of the apsim model for irrigated maize–signalgrass intercropping system (Acta Scientiarum. Agronomy, 2026)
The Agricultural Production Systems Simulator (APSIM) has been widely used in studies to simulate the growth and development of pastures and grain crops in single-crop and intercropping cultivation systems. The objective of this study was to parameterize the APSIM and evaluate its effectiveness in estimating the growth and productivity of maize and signalgrass (Urochloa ruziziensis) in single-crop and intercropping systems in northern Piauí State, Brazil. Data were collected from the experimental field of the Brazilian Agricultural Research Corporation (Embrapa Mid-North) in Teresina, Piauí State, Brazil. The photosynthetically active radiation and soil water content were the main measurement parameters to calibrate the light extinction coefficient and radiation use efficiency, with adjustments to the phenological and structural parameters of maize. The leaf, stalk, and total shoot dry weights and leaf area index (LAI) of both crops and maize organs (husk, cob, and grains) were evaluated. The model showed coefficient of determination (R2) values ranging from 0.81 to 0.99 and Nash–Sutcliffe efficiency (NSE) values ranging from 0.72 to 0.99 for single-crop cultivation of signalgrass; R2 values ranging from 0.87 to 0.93 and NSE values ranging from 0.62 to 0.67 for intercropping cultivation of signalgrass; R2 values ranging from 0.43 to 0.97 and NSE values ranging from -3.33 to 0.95 for single-crop cultivation of maize; and R2 values ranging from 0.30 to 0.93 and NSE values ranging from 0.21 to 0.92 for intercropping cultivation of maize. The APSIM model provided an adequate fit for growth simulations of signalgrass and maize in single-crop and intercropping systems. It can simulate the growth and yield of irrigated signalgrass and maize in single-crop and intercropping systems.